Syarat dan Masa Jabatan Pimpinan KPK Perspektif Islamic Constitusionalism (Analisis Putusan MK No.112/PUU-XX/2022) - Kurniawan, Yusuf Fendi; Santoso, Lukman (Constitution Journal, 2024)
Based on Article 24C of the 1945 Constitution, the Constitutional Court has the authority to conduct judicial review of laws against the 1945 Constitution, known as judicial review. The Constitutional Court's decision usually rejects several applications that change the norms of the Law on the grounds of open legal policy which is the authority of the lawmakers. This research aims to explore the legal reasoning of judges in interpreting the 1945 Constitution in Constitutional Court Decision Number 112/PUU-XX/2022 which amended Article 29e of Law 19/2019 and Article 34 of Law 30/2002, as well as the implications of the decision for the existence of the Corruption Eradication Commission (KPK) from the perspective of Islamic constitutionalism. This research uses statutory and conceptual approaches. This study found that the testing of Article 29e of Law 19/2019 and Article 34 of Law 30/2002 is more inclined to non-originalism, judicial activism, and prudential interpretations that involve political calculations and inconsistencies. The implications of Constitutional Court Decision No. 112/PUU-XX/2022 on the existence of the KPK from the perspective of Islamic Constitutionalism lead to an unfair KPK leadership appointment process, so that the effectiveness of the KPK in eradicating corruption can be disrupted, threatening public justice and potentially creating injustice. This study contributes to strengthening the implementation of the separation of powers and the implementation of the principle of checks and balances in Indonesia. Abstrak Berdasarkan Pasal 24C UUD 1945, Mahkamah Konstitusi memiliki kewenangan untuk melakukan uji materiil terhadap Undang-Undang terhadap Undang-Undang Dasar 1945, yang dikenal sebagai judicial review. Putusan Mahkamah Konstitusi lazimnya menolak beberapa permohonan yang mengubah norma UU dengan alasan open legal policy yang merupakan kewenangan pembuat Undang-Undang. Penelitian ini bertujuan untuk menggali nalar hukum hakim dalam menafsirkan UUD 1945 dalam putusan MK Nomor 112/PUU-XX/2022 yang mengubah pasal 29e UU 19/2019 dan pasal 34 UU 30/2002, serta implikasi putusan tersebut terhadap keberadaan Komisi Pemberantasan Korupsi (KPK) dari perspektif Islamic constitutionalism. Penelitian ini menggunakan pendekatan perundang-undangan dan konseptual. Penelitian ini menghasilkan temuan bahwa pengujian pasal 29e UU19/2019 dan pasal 34 UU 30/2002 lebih condong pada non-originalism, judicial activism, dan penafsiran prudensial yang melibatkan kalkulasi politik dan inkonsisten. Implikasi putusan MK Nomor 112/PUU-XX/2022 terhadap eksistensi KPK dari perspektif Islamic Constitutionalism mengarah pada proses penunjukan pimpinan KPK yang tidak adil, sehingga efektivitas KPK dalam memberantas korupsi dapat terganggu, mengancam keadilan masyarakat dan berpotensi menciptakan kezaliman. Kajian ini berkontribusi untuk penguatan pelaksanaan pemisahan kekuasaan dan pelaksanaan prinsip check and balances di Indonesia.